Pemodelan Struktur Bawah Permukaan Kabupaten Rejang Lebong dengan Metode Inversi 3D Data Gravitasi Satelit Menggunakan Koreksi SRTM2gravity - Puja Kasmailen Putri; Ahmad Fauzi pohan; Marzuki Marzuki (Universitas Andalas, 2024)
Rejang Lebong is a tourism area in Bengkulu Province, Indonesia, which is located close to the active Ketaun and Musi faults which are segments of the Sumatran Fault System (SFS). This research uses 3-D analysis and modeling of Earth's gravity anomaly inversion data obtained from the high-resolution Global Gravity Model (GGM). The aim of this research is to identify subsurface geological structures such as faults, active volcanoes and sedimentary layers that have the potential to pose a danger to the Curup Rejang Lebong tourism area. The Complete Bouguer Anomaly (CBA) in the study area was calculated using modern terrain correction methods that utilize full-scale topographic gravity data from the SRTM2gravity model. Separating regional and residual anomalies using an upward continuity filter with a height of 10 km. The 3D inversion model of satellite gravity data has succeeded in modeling the subsurface of the Rejang Lebong district where the presence of the Mount Kaba magma chamber is characterized by low negative density contrast, and the Ketaun and Musi fault lines are characterized by low and high contrast boundaries which have the potential to cause natural disasters in the region. Analysis of gravity anomalies and rock density contrasts provided results that are in line with the regional geological conditions of the Bengkulu region, including the pattern of intrusion of igneous rocks with high density contrasts and sedimentary rocks with lower density contrasts.